SOR Framework on Customer Engagement by Using Influencer Marketing in E-Commerce Affiliate Program - Rifa Safitri, Erina; Masnita, Yolanda; Kurniawati, Kurniawati (Tekmapro, 2025)
This study explores the use of influencer marketing in e-commerce affiliate programs to enhance customer engagement, utilizing the Stimulus-Organism-Response (SOR) framework. The research model incorporates the commercial orientation of influencer Instagram posts, trust in influencers, and purchase intention as key variables. Data analysis and hypothesis testing reveal significant influences, indicating that influencer content on Instagram substantially impacts consumer trust and purchase intention. The findings underscore the potential of influencer marketing strategies to build consumer trust and influence purchasing decisions. The study's insights provide valuable implications for e-commerce businesses seeking to leverage influencer marketing for enhanced customer engagement and brand promotion. Keywords: Affiliate Program, Instagram, Influencer Marketing, SOR Framework, E-commerce